Wind integration into hydro dominant Power System - Thorleiksson, Johannes (My University, 2013)
The Icelandic Power System is a hydro dominant system where approximately 75 % of the electricity generation is hydro based. However due to transmission constraints the potential of this mean of generation can not be fully utilised. In the eastern part of Iceland, in the last years, the consumption of electricity has been increasing. This has led to increased stress on the transient stability limits of the system. In recent years there has been a growing interest of wind power in Iceland. However the impact of wind generation on the system stability has not been assessed. In this thesis the impact of wind generation, in the east area, on the transient stability of the system is analysed and supplementary control based on wide area measurements is implemented to aid the transient stability of the system. This Master thesis was done in cooperation with Landsvirkjun, Landsnet and ABB Switzerland.
Keywords: Elkraftteknik; Electric power engineering